Influence of acupuncture on neural movement function in rats with middle cerebral artery occlusion-A randomized controlled trial - 常晓波 樊小农 王舒 杨沙 杨雪 张亚男 石学敏 (Journal of traditional Chinese medicine, 2012)
OBJECTIVES：To observe recovery in movement function in rats with middle cerebral artery occlusion（MCAO） after acupuncture treatment.METHODS：According to the randomized and controlled principle 1384 rats were divided into the ba-sic control group（including the normal,sham,model control,model without intervention,Nimodipine,and para-Renzhong groups） and the acupuncture group（including the Neiguan（PC 6）,Weizhong（BL 40）,Sanyinjiao（SP 6）,Chize（LU 5）,Renzhong（GV 6） and non-acupoint groups）.MCAO was modeled by Zea-longa＇s thread ligation and rats with scores of 1-3,as assessed by Zausinger＇s six-point method,were used in this study.Moreover,in the acupuncture group each acupoint was set with 12 different parameters by the orthogonal intersection method,resulting in 78 groups with 18 rats per group.The rats were treated by acupuncture once every 12 h for a total of six sessions and neurobehavioral scores were measured after each session.The neurobehavioral scores were compared by one-way ANOVA using the statistical software SPSS 17.0.RESULTS：After acupuncture therapy the mean neurobehavioral scores in MCAO rats increased gradually at each time point with a significant difference among the six scores,but with no significant differences between the fourth（48 h） and the fifth score（60 h）,and between the fifth（60 h） and the sixth（72 h） score（P 0.05）.CONCLUSIONS：MCAO rats gradually recovered movement function over multiple acupuncture sessions.After the fouth acupuncture session（48 h）,the neurobehavioral scores of rats with cerebral infarction remained stable.Acupuncture treatment had a reliable curative effect on movement function in cerebral infarction rats.